Limonin Exhibits Anti-Inflammatory Effects by Inhibiting mTORC1 and Mitochondrial Reactive Oxygen Species in Psoriatic-like Skin Inflammation - Seung Taek Lee; Jong Yeong Lee; Ha Eun Kim; Jun-Young Park; Jin Kyeong Choi (Antioxidants)
Psoriasis is a chronic inflammatory skin disorder characterized by abnormal immune responses and keratinocyte hyperproliferation. Limonin, a bioactive compound found in citrus fruits, has anti-inflammatory properties in various models; however, its effects on psoriasis are not fully understood. We investigated the therapeutic potential of limonin in a 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced psoriasis mouse model. Mice were treated with TPA to induce psoriasis-like skin lesions, followed by intraperitoneal administration of limonin (200 or 400 μg/mouse) for six days. The results showed that limonin improved psoriasis-related symptoms in a psoriasis-like mouse model by suppressing the mRNA expression of pro-inflammatory cytokines and inflammation-related antimicrobial peptides and regulating the expansion of myeloid cells and T cells. Specifically, limonin reduced glucose uptake and oxidative phosphorylation to shift the metabolic program in the inflamed skin cells of psoriasis-like mice. Limonin activates AMPK and proteins related to mTOR inhibition, thereby suppressing the mTOR signaling pathway. It also inhibits mitochondrial mass and mitochondrial ROS production, thereby preventing the development of dysfunctional mitochondria in inflamed skin cells. Overall, limonin modulates key immune responses and metabolic pathways related to inflammation and mitochondrial health in psoriasis. Therefore, it is a promising natural candidate for the treatment of psoriasis and various inflammatory skin diseases.